Actinomyces neuii subsp. neuii Isolated from Perineal Abscess; Case Report - Emel AKBAŞ (Bezmiâlem Science, 2019)

(untitled)
Actinomyces are gram positive bacilli which generally colonize in mouth, colon and vagina. The members of genus Actinomyces are facultative anaerobic or microaerophilic organisms and have a branching flamentous structure. They cause classical actinomycosis. Among the Actinomyces species; A. israelii, A. viscosus, A. naeslundii, A. odontolyticus, A. bovis and A. neuii are the mostly isolated organisms from clinical cases. A rarely encountered member of this group, Actinomyces neuii does not show branching and is catalase and CAMP positive and is a coryneform shaped bacillus. Although Actinomyces is mostly found as contaminating organism, in some cases it is reported as a pathogen. Actinomyces neuii has been reported in chorioamnionitis, neonatal sepsis, vertebral osteomyelitis, cervical lymphadenitis, breast abscess, fatal bacteremia and postoperative endophthalmitis. In our case, A. neuii was isolated from a perineal abcess and it was not previously reported. In our case, Actinomyces neuii was identified by commercial identification systems. For this purpose; VITEK MS and VITEK®2 Compact (both by bioMérieux, France) were used in the clinical microbiology laboratory and then this identification was confirmed as the Actinomyces neuii subsp. neuii by the 16S rRNA sequencing. Also, the positivity of CAMP was demonstrated in the laboratory. As in the cases of other actinomycosis, the treatment of the abcess caused by the Actinomyces neuii is through the surgical debridement. The antimicrobial susceptibility testing is not performed since the organism is reported to be susceptibile to common antibiotics. Beta lactam antibiotics are acknowledged as the proper selection for antibiotic treatment.